2018
DOI: 10.1080/10826084.2018.1461222
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Goal Trajectories and Their Association with Client Characteristics and Outcomes among Clients in Outpatient Alcohol Treatment

Abstract: Since the majority of clients maintain their initially selected drinking goal, counsellors might inform them at treatment admission about the various probabilities of achieving nonhazardous drinking depending on their selected drinking goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…A more general notion can be made, namely that individuals who do not have a history of prior treatment aim for controlled drinking goals. This notion supports the literature ( Haug et al, 2018 ; Haug et al, 2017 ) which finds that patients, in general, aim for controlled drinking. If, however, prior treatment has not led to the ability to control their drinking, the patients may adjust to the situation and/or resign and aim for permanent abstinence instead.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A more general notion can be made, namely that individuals who do not have a history of prior treatment aim for controlled drinking goals. This notion supports the literature ( Haug et al, 2018 ; Haug et al, 2017 ) which finds that patients, in general, aim for controlled drinking. If, however, prior treatment has not led to the ability to control their drinking, the patients may adjust to the situation and/or resign and aim for permanent abstinence instead.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, abstinence as a goal in treatment for alcohol use disorder (AUD) seems to lead to the largest proportion of patients with successful outcomes ( Dunn & Strain, 2013 ), where relatively fewer patients seem to be successful in treatment with controlled drinking goals ( Meyer, Wapp, Strik, & Moggi, 2014 ). Although patients’ goals for treatment may change during the course of treatment for AUD ( Haug, Castro, Eggli, & Schaub, 2018 ; Meyer et al, 2014 ), most patients seem to strive for controlled drinking goals ( Haug et al, 2018 ; Haug, Eggli, & Schaub, 2017 ), particularly in the early stages of treatment. In the mid-1980s Orford and Keddie (1986) showed that self-selected goals were predictive for positive treatment outcome.…”
mentioning
confidence: 99%
“…Although previous studies on text message-based interventions in patients with AUD have shown significantly better alcohol-related outcomes compared with the control group (Agyapong et al, 2018;Haug et al, 2018), we could not replicate these results. The inconsistent results might be caused by the different alcohol-related outcomes, different modalities of the interventions applied, or different patient samples in the studies.…”
Section: Interventioncontrasting
confidence: 74%
“…findings were also consistent when abstainers were excluded, thus ruling out the possibility that abstinence is the critical driver of functional improvement. Many individuals seeking treatment for alcohol problems prefer non-abstinence goals [7,8], and more individuals may become interested in treatment if drinking reduction goals are included as a treatment target [49,50]. Treatment providers may also help to reduce harm caused by alcohol by talking with patients about drinking reductions, including non-abstinent reductions.…”
Section: Predictormentioning
confidence: 99%
“…The inclusion of harm reduction end-points is important, because most individuals who receive treatment for AUD have difficulty sustaining abstinence [4][5][6] and many individuals with AUD prefer drinking reduction goals [7][8][9][10][11]. However, questions remain regarding whether non-abstinent drinking reductions can be achieved and maintained, particularly among individuals with more severe AUD [12,13].…”
Section: Introductionmentioning
confidence: 99%